Phytochemicals analysis and antibacterial activity of the leaf of red meranti, Shorea leprosula (Dipterocarpaceae) - SUDRAJAT SUDARAJAT; DWI SUSANTO; RUDI KARTIKA (Nusantara Bioscience, 2016)
Abstract. Sudrajat, Susanto D, Kartika R. 2016. Phytochemicals analysis and antibacterial activity of the leaf of red meranti, Shorea leprosula (Dipterocarpaceae). Nusantara Bioscience 8: 111-116. This study aims to investigate the antibacterial activity of the total ethanolic extract and its fractions of red meranti (Shorea leprosula) leaf against Gram-positive bacteria Staphylococcus aureus and Gram-negative bacteria Escherichia coli. The ethanolic extract and its fractions were subjected to antibacterial assay using well diffusion technique. Column chromatography was used to purify the active compounds from the mixture, while GC/MS was used to identify the phytocomponents of the fractions. The GC/MS study demonstrated the presence of different types of compounds were 1,2-benzenedicarboxylic acid (65.77%), eicosanoic acid (9.82%), 2-pentadecenone (6.53%), tricosane (5.86%) and hexanedioic acid (4.13%). The result showed that the inhibition zone diameters of the ethanolic extracts ranged from 15.56-16.44 mm against S. aureus, and 15.37-16.56 mm for E. coli, respectively. The total ethanolic extract from red meranti leaf showed a strong category of antibacterial properties against both types of bacteria which were equivalent to antibiotic chloramphenicol. While, the fractions extracts showed that antibacterial activity was lower than total ethanolic extract against Gram-positive bacteria S. aureus and Gram-negative bacteria E. coli. The results obtained from this study justify the use of this plant in traditional medicine and provide leads which could be further exploited for the development of new and potent antibacterial.